Digestive Diarrhea Syndrome In Children Under One Year Of Age - Temirova Aydin Husan kizi (Zien Journals, 2025)
Almost every article devoted to the condition of the gastrointestinal tract (GIT) in young children begins with a phrase about the high frequency of occurrence of disorders of the digestive system in the first year of life. In case of functional disorders (FD) of the GIT, digestion and absorption of food, motor function, composition of the intestinal microbiota and activity of the immune system change. The causes of FD often lie outside the affected organ and are caused by a violation of the nervous and humoral regulation of the digestive tract
Keywords: functional disorders; regurgitation in infants; rumination syndrome in infant